A novel magneto-rheological fluid dual-clutch design for two-speed transmission of electric vehicles. (17th June 2021) - Zhang, Huan; Du, Haiping; Sun, Shuaishuai; Zhao, Jin; Ning, Donghong; Li, Weihua; Wang, Yafei
Abstract: The dual-clutch transmission (DCT) in electric vehicles can significantly decrease the torque interruption and improve the shifting comfort. The magneto-rheological fluid (MRF) is a kind of intelligent material commonly used for torque transmission devices with high control accuracy and fast response, e.g. MRF clutch. This paper proposes a novel MRF dual-clutch (MRFDC) design for the two-speed transmission of EVs combining the DCT and MRF clutch advantages. The MRFDC is composed of an internal clutch and an external clutch. The two clutches with the same input shaft and different output shaft can shift between two gears by controlling the input current through the coils in the two clutches. The relationship between the input current and the magnetic flux density is obtained by the finite element analysis of the magnetic field under different input current. Theoretical analysis is carried out to estimate the output torque of MRFDC according to the geometric dimensions of MRFDC structure and rheological properties of MRF. The Herschel-Bulkley model is applied to describe the MRF behaviour because the shear rate of MRF is relatively high. The output torque model is built considering the magnetic flux density. Therefore, the relationship between the transmissible torque and applied input current is determined. Finally, the MRFDC model is experimentally verified on the testbed; besides, the transmissible torque tests and response time tests for internal and external MRF clutches are carried out, respectively. The test results agree with the simulation results, and the differences are within 2 N m. It is suggested that the MRFDC can be applied in EVs to improve vehicle performance.